Legal Reasoning of a Judge’s Dissenting Opinion in the Decision of the Constitutional Court No. 1/PUU-VIII/2010 Against the Judicial Review of Law No. 3 of 1997 on Juvenile Courts - Hilman Syahrial Haq; Sofyan Wimbo Agung Pradnyawan; M Taufik Rachman; Edi Yanto; Anies Prima Dewi; Jan Alizea Sybelle (Jurnal Jurisprudence, 2022)
ABSTRACT Purpose of the study: This paper aims to analyze the judicial considerations of the dissenting opinion of Constitutional Court judge member Akil Mochtar on Constitutional Court No. 1/PUU-VIII/2010 Against the Judicial Review of Law No. 3 of 1997 on Juvenile Courts. Methodology: This normative research was based on literary sources. It aimed to discuss the problems that have been formulated to then obtain the expected results. To maximize discussion, this study uses a statute approach and other concepts obtained from literary sources.  Results: The dissenting opinion conveyed by judge member Akil Mochtar only discussed the law as a written rule in the application of the law. Meanwhile, the Constitutional Court attempted to find substance in the Constitutional Court's decision. People's need for justice encourages constitutional judges as law enforcers to make various breakthroughs considering that the Constitutional Court's decisions are final and binding and have a general influence on the legal system. Observing the age range of children in Law No. 3 of 1997, which is between 8 and 18 years, legal provisions indirectly consider children in that age range to be able to commit criminal acts so that they can be sentenced like adults. In human development, a person of 8 years is still said to be immature (minderjarig) or still unable to be responsible. They have imperfect knowledge of the causes and consequences of their actions committed. Mistakes and wrongdoing should be considered child delinquency rather than a crime. Applications of this study: This paper can be applied by the Constitutional Court to make betterment to laws that are proposed for review by attempting to find the legal substance. Novelty/ Originality of this study: No previous researchers have studied the dissenting opinion in this decision  Keywords: Constitutional Court, Juvenile Court, dissenting opinion, judicial review, legal reasoning.  ABSTRAK  Tujuan: Tulisan ini bertujuan untuk menganalisis pertimbangan yuridis atas dissenting opinion anggota hakim Mahkamah Konstitusi Akil Mochtar tentang Mahkamah Konstitusi No. 1/PUU-VIII/2010 Terhadap Uji Materi Undang-Undang No. 3 Tahun 1997 tentang Peradilan Anak .  Metodologi: Penelitian normatif ini didasarkan pada sumber literatur. Hal ini bertujuan untuk membahas masalah yang telah dirumuskan untuk kemudian memperoleh hasil yang diharapkan. Untuk memaksimalkan pembahasan, kajian ini menggunakan pendekatan undang-undang dan konsep lain yang diperoleh dari sumber normative.  Hasil: Dissenting opinion yang disampaikan oleh anggota hakim Akil Mochtar hanya membahas undang-undang sebagai aturan tertulis dalam penerapan undang-undang. Sementara itu, Mahkamah Konstitusi berupaya mencari substansi dalam putusan Mahkamah Konstitusi tersebut. Kebutuhan masyarakat akan keadilan mendorong hakim konstitusi sebagai penegak hukum melakukan berbagai terobosan mengingat putusan MK bersifat final dan mengikat serta berpengaruh secara umum terhadap sistem hukum. Mencermati rentang usia anak dalam UU No. 3 Tahun 1997, yaitu antara 8 hingga 18 tahun, ketentuan hukum secara tidak langsung menganggap anak dalam rentang usia tersebut dapat melakukan tindak pidana sehingga dapat dipidana seperti orang dewasa. Dalam perkembangan manusia, seseorang yang berumur 8 tahun masih dikatakan belum dewasa atau masih belum mampu bertanggung jawab. Mereka memiliki pengetahuan yang tidak sempurna tentang sebab dan akibat dari tindakan yang mereka lakukan. Kesalahan harus dianggap sebagai kenakalan anak daripada kejahatan.  Kegunaan: Kajian ini dapat digunakan oleh Mahkamah Konstitusi untuk melakukan perbaikan terhadap undang-undang yang diajukan untuk diuji dengan mencoba menemukan substansi hukumnya.  Kebaruan/ Orisinalitas: Belum ada penelitian sebelumnya yang mempelajari dissenting opinion dalam putusan ini  Kata Kunci: Mahkamah Konstitusi, Pengadilan Anak, Dissenting Opinion, Peninjauan Kembali, Penalaran Hukum